Ammonium inhibits processing and cytotoxicity of reovirus, a nonenveloped virus. - Maratos-Flier, E (1986)
Successful viral infection involves a series of interactions between the virus and the host cell. The outcome of viral infection is, in fact, dependent on intact cellular function; it is required for viral binding, internalization, and uncoating. To determine the potential importance of lysosomal processing on the outcome of infection with a nonenveloped virus, we have studied the effects of NH4Cl on the course of reovirus infection on a beta-cell tumor in culture. Addition of 10 mM NH4C1 to the medium inhibited viral growth by greater than 80% and reduced toxic effects of the virus on cell viability, protein, and DNA synthesis by 30-45%. In addition, synthesis of viral proteins was markedly decreased. Uptake of virus prelabeled with [35S]methionine was not affected by the ammonium; however, cleavage of mu1C, an outer capsid protein of the virus whose cleavage appears to be required for viral replication, was delayed. These results suggest that intracellular processing of reovirus is dependent on a lysosomal pathway and that disruption of this pathway can alter the course of viral infection.